Revista Ponto de Acesso (ICI/UFBA) – v. 8, n. 3 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número: http://www.portalseer.ufba.br/index.php/revistaici/issue/view/1027